Experiences in macroeconomic forecasting in the Federal Republic of Germany, 1976-1987 - Enno Langfeldt; Peter Trapp (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1988)
There have always been fluctuations of production, employment, and prices in economic history. A lot of strenuous work and intellectual efforts have been put into the study of these fluctuations. Huge amounts of time series data have been collected and indicators have been compiled to determine cyclical regularities and to provide information on the cycle (see for example Burns and Mitchell, 1946). And many attempts have been made to explain the forces behind the ups and downs of economic activity (see Zarnowitz, 1985). Whereas originally business cycle research was mainly directed at understanding the fluctuations, research objectives became more practical after the shock of the Great Depression. The experience of the strong and protracted economic downturn enhanced the call for a more active role of the government in supporting economic growth and in maintaining a high level' of employment. Keynes1 General Theory (1936) delivered the theoretical basis for this policy.
Keywords: 330; Konjunkturprognose; Wirtschaftsprognose; Deutschland